Sustainable Technologies and Drivers for Managing Plastic Solid Waste in Developing Economies - Mwanza, Bupe G.; Mbohwa, Charles; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book discusses sustainable waste management technologies for managing end-of-life (EoL) post-consumer and packaging plastic solid waste (PSW) from domestic and commercial waste streams. It does so particularly in the context of providing a way forward for developing economies. Treating recycling and composting of, and energy recovery from, plastics, the book is directed at individuals who are responsible for or have a significant role in solid waste management. Academics and students in solid waste management pursuing research or study in solid waste management with particular interest in plastics will find this book useful. Sustainable options for managing PSW are presented with reference to the scientific, engineering, and management standpoints to enable decision makers and relevant stakeholders in industry arrive at the best decision for achieving sustainable resource management. The book further integrates waste management and technologies so that PSW recycling can be viewed from environmental, economic, and social perspectives. Greener technologies for PSW management are addressed so as to provide drivers that will influence key stakeholders and policy-makers achieve sustainability in this field.
Introduction -- Post-Consumer Plastic Solid Wastes -- Technologies for Managing Plastic Solid Wastes -- Sustainability in Post-Consumer PSW Management Technologies -- Drivers to Sustainable Post-Consumer PSW Management in Developing Economics -- Policy-Makers' Responsibilities -- Contributions.
Keywords: Manufactures; Refuse and refuse disposal; Environmental sciences$1 (BSocial aspects.s; Energy policy; Energy and state; Development economics; Economic development; Machines, Tools, Processes; Waste Management/Waste Technology; Environmental Social Sciences; Energy Policy, Economics and Management; Development Economics; Development Studies; Plastic scrap -- Developing countries